Assessment of Cysteine Reactivity of Human Hemoglobin at Its Residue Level: A Mass Spectrometry-Based Approach. (2nd November 2017) - Mitra, Amrita; Muralidharan, Monita; Srivastava, Deepsikha; Das, Rajdeep; Bhat, Vijay; Mandal, Amit K.
Abstract: In general, the reactivity of cysteine residues of proteins is measured by 5, 5′-dithiobis(2-nitrobenzoic acid) (DTNB) kinetics using spectrophotometry. Proteins with several cysteine residues may exhibit varying DTNB kinetics but residue level information can only be obtained with the prior knowledge of their three-dimensional structure. However, this method is limited in its application to the proteins containing chromophores having overlapping absorption profile with 2-nitro-5-thiobenzoic acid, such as hemoglobin (Hb). Additionally, this method is incapable of assigning cysteine reactivity at the residue levels of proteins with unknown crystal structures. However, a mass spectrometry (MS)-based platform might provide a solution to these problems. In the present study, alkylation kinetics of cysteine residues of adult human Hb (Hb A; α2 β2 ) and sickle cell Hb (Hb S; HBB : c.20A>T) were investigated using matrix-assisted laser desorption/ionization (MALDI) MS. Differential site-specific reactivities of cysteine residues of Hb were investigated using alkylation kinetics with iodoacetamide (IAM). The observed reactivities corroborated well with the differential surface accessibilities of cysteine residues in the crystal structures of human Hb. The proposed method might be used to investigate cysteine reactivities of all the genetic and post-translational variants of Hb discovered to date. In addition, this method can be extended to explore cysteine reactivities of proteins, irrespective of the presence of chromophores and availability of crystal structures.